Transformational Leadership, Work Ethos, and Motivation in Enhancing Civil Servant Teacher Performance in Northern Cianjur - Yurnita, Fitri; Irdiansyah, Iyan; Chaniago, Syahril (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
This study aims to analyze the determinants of teacher performance among State Civil Servant (ASN) senior high school teachers in the Northern Region of Cianjur Regency. Grounded in the Integrative Model of Organizational Behavior by Colquitt, this research specifically examines the effects of transformational leadership and work ethos, with the mediating role of work motivation. Employing a quantitative explanatory research design, data were collected from 223 ASN senior high school teachers using a structured questionnaire distributed through proportional random sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results demonstrate that transformational leadership and work ethos have a positive and significant effect on teacher performance. A crucial finding proves that work motivation functions as a significant mediating variable, acting as a catalyst that translates managerial stimuli into tangible performance. The model exhibits strong predictive power with R2 values of 0.695 for Work Motivation and 0.684 for Teacher Performance. These findings suggest that strengthening transformational leadership and fostering a positive work ethos are essential for optimizing teacher professionalism in a digital administrative environment.